Our Germans : project paperclip and the national security state - Crim, Brian E. (Johns Hopkins University Press, 2018)
"Our Germans is a highly engaging history of one of the United States' most controversial intelligence operations during the early Cold War. Project Paperclip brought fifteen hundred German scientists and their dependents to the United States in the first decade after World War II. More than the freighters full of equipment and documents recovered from caves and hastily abandoned warehouses, the "German brains" who designed and built the V-2 rocket and other "wonder weapons" for the Third Reich proved invaluable to America's emerging military-industrial complex. Whether they remained under military employment, transitioned to civilian agencies like NASA, or sought more lucrative careers with corporations flush with government contracts, German specialists recruited into the Paperclip program assumed enormously influential positions within the labyrinthine national security state."--Provided by publisher